Learning the culture of entrepreneurship - Sibayan, Salvador I. (2007)
This research aimed to determine what conditions influence people to go to entrepreneurship, how entrepreneurship is learned, what entrepreneurial characteristics are learned through time, meanings of the learning process, and what commonality exists among entrepreneurs. The study documented the transformation of non-entrepreneurs to entrepreneurs by doing participant observation in the Junior Achievement Philippines, Inc. and gathering the life histories of six entrepreneurs through interviews. It was found that their choice of business was influenced by their previous experience. At certain stages of their business, they had mentors and act or react depending on the circumstances. Entrepreneurship opens opportunities to a better life and at the same time involves life-long learning.